Documenting the Physical and Psychological Consequences of COVID-19 - Ghaffarzadeh Namazi , Reza; Mohseni Rad, Aghil; Isamorad , Aboalghasem (Health Nexus, 2024)
The coronavirus (COVID-19) represents a public health crisis that has imposed numerous restrictions on daily activities. The crisis conditions created by COVID-19 can lead to negative physical and psychological effects on society. In this context, the present study aims to document the physical and psychological consequences of COVID-19 using a qualitative grounded theory approach. This study is applied in its aim and qualitative in nature. The strategy employed in this research is the grounded theory method. The statistical population and sample of this study consisted of 11 individuals infected with COVID-19, who were selected through accessible and purposive sampling due to the nature of the research. This study was conducted using semi-structured interviews with COVID-19 patients until the point of data saturation was reached, and the data obtained from the interviews were subsequently analyzed. Based on the findings, the physical consequences of experiencing COVID-19 included fatigue and lethargy, severe and indescribable pain, an enhanced immune system, and restricted activities. On the other hand, the psychological consequences included experiencing anxiety, family cohesion, existential anxiety (fear of death), strengthened connection with God and spirituality, and deepened relationships. The findings of this study support the notion that every crisis has another side, which includes opportunities that arise during and after the confrontation with the crisis, providing conditions for further growth and development. Therefore, alongside necessary actions and measures such as stress and anxiety management training to prevent the compounded effects of the disease and its associated anxiety, it is also essential to leverage the positive opportunities and outcomes presented by this crisis (COVID-19).